OPTIMALISASI PENDIDIKAN ANAK DESA SUMBERPITU SEBAGAI UPAYA PENYIAPAN SUMBER DAYA MANUSIA UNGGUL - mohammad rizal; Arini Fitria Mustapita (Universitas Islam Malang, 2022)
This service aims to increase the human resource in Sumberpitu Village, Pasuruan Regency. As the basic capital for implementing development in Sumberpitu Village, human resources are absolutely necessary to support the achievement of a well-planned village development program. As the main actor in the implementation of development in the village, of course the participation and carrying capacity of human resources is the most important part of the success of the implementation of development. The methods implemented in this activity are methods: counseling, socialization, training, and coaching to the community, especially for school-age children. The results of this service indicate that the materials provided support the activities of increasing the workforce and the materials provided by the service team are delivered and well received by the participants.